Estética prospectiva, trágico colonial e imaginación política: aproximaciones iniciales entre Um defeito de cor, de Ana Maria Gonçalves, y Changó, el gran putas, de Manuel Zapata Olivella (Dossier Literatura brasileña y latinoamericana: cruce de lecturas) - Ramos, Marcos Alexandre do Amaral (2025)
This article analyzes Um defeito de cor, by Ana Maria Gonçalves, and Changó, el gran putas by Manuel Zapata Olivella as Afrodiasporic narratives that destabilize the framework of Western history and confront the Colonial Tragic. The aim is to demonstrate how these works reconfigure historical memory through marginalized voices, employing strategies such as critical fabulation, mythopoetics, and spirituality as tools of resistance and emancipation. The methodology is based on a comparative analysis of both works, drawing on concepts such as repression, sublimation, and Prospective Aesthetics, while engaging with theorists like Saidiya Hartman, Walter Mignolo, and Achille Mbembe. The findings reveal that both narratives function as counter-devices, shifting the Eurocentric axis of history and reinscribing Afrodiasporic agency. African spirituality emerges as a central axis—not only as a theme but as a decolonizing practice that envisions alternative futures. The article concludes that by rewriting the past, these works challenge the coloniality of knowledge and open pathways for the construction of emancipatory identities and horizons.